2017
DOI: 10.1038/srep45589
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pancreatic Cyst Types by Analysis of Rheological Behavior of Pancreatic Cyst Fluid

Abstract: Differentiation between mucinous and non-mucinous pancreatic cysts is exceedingly important and challenging, particularly as the former bears malignant transformation potential. Pancreatic cyst fluid (PCF)-based diagnostics, including analyses of biochemical markers, as well as cytology, has shown inadequate accuracy. Herein, a preliminary single-center study of 22 PCF samples, collected by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA), assessed the rheological behavior of PCF and its correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This mixture consisted of an artificial mucus matrix product to which pancreatic enzyme extracts were added. The viscosity of this matrix was adjusted to 1.5 cP, based on previous rheology studies of pancreatic cyst fluid [ 37 ]. Recombinant pepsinogen C was diluted with this matrix at varied concentrations and used for gastricsin activity assays.…”
Section: Resultsmentioning
confidence: 99%
“…This mixture consisted of an artificial mucus matrix product to which pancreatic enzyme extracts were added. The viscosity of this matrix was adjusted to 1.5 cP, based on previous rheology studies of pancreatic cyst fluid [ 37 ]. Recombinant pepsinogen C was diluted with this matrix at varied concentrations and used for gastricsin activity assays.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] However, the diagnostic accuracy, sensitivity, and specificity of the CEA level in cyst fluid vary according to the CEA cutoff. [ 15 16 ] Brugge et al . showed that with cyst fluid CEA cutoff level of 192 ng/ml has sensitivity of 75%, specificity of 83.6%, and diagnostic accuracy of 79% in differentiating mucinous from non-MPCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study,[ 2 ] we found that the cutoff value of pancreatic cyst fluid viscosity, ηc, can serve as an independent marker to distinguish between mucinous and non-mucinous cysts. It was found that ηc >1.3 cP characterizes mucinous cysts, whereas ηc >1.3 cP is typical for non-mucinous cysts.…”
mentioning
confidence: 86%